A MUCINOUS CYSTADENOMA ORIGINATED FROM MESENTERY -A CASE REPORT - KIMURA, Norihisa; MOROHASHI, Hajime; KOYAMA, Motoi; MURATA, Akihiko; KURUSHIMA, Michihiro; SASAKI, Mutsuo (Nihon Rinsho Geka Gakkai Zasshi (Journal of Japan Surgical Association), 2005)
A 51-years-old woman received an examination complaining of the right abdominal pain. Abdomi-nal computed tomography showed a homogeneous, non-enhanced cystic tumor of about 10cm in diameter in the ileo-cecal mesentery. Colonoscopic study did not reveal mucosal lesion, nor luminal compression from outside. Angiography showed non-vascular area of the ileo-cecum. An operation was performed under the diagnosis of mesenteric lymphangioma. In operative findings, the tumor was 9×8×7cm in size and existed in the ileo-cecal mesentery. We performed ileo-cecal resection including 100cm of ileum, because the tumor had severe adhesion to the ileal wall. The resected specimen had multi-cystic lesion in part and contained green mucinous fluid. The histopathological diagnosis was mucinous cystadenoma. ER, PgR, and CA125 staining was positive that suggested the tomor originated from the female reproductive organ, such as ectopic ovarian tissue or secondary Mullerian system. We report a rare case of mucinous cystadenoma originated from ileo-cecal mesentery with a review of the literatures.